Functional Recognition by CD8+ T Cells of Epitopes with Amino Acid Variations Outside Known MHC Anchor or T Cell Receptor Recognition Residues - Wilson, Kirsty L. (Int J Mol Sci, 2020)
Peptide-based vaccines can be safer and more cost effective than whole organism vaccines. Previous studies have shown that inorganic polystyrene nanoparticles (PSNPs) covalently conjugated to the minimal immunodominant peptide epitope from murine liver stage malaria (SYIPSAEKI) induced potent CD8+ T cell responses. Many pathogens, including malaria, have polymorphic T cell epitope regions. Amino acid changes in positions that are contact residues for the T cell receptor (TCR) often alter the specific cross-reactivity induced by the peptide antigen, and it is largely assumed that changes outside of these residues have little impact. Herein, each amino acid residue (except major histocompatibility complex (MHC) anchors) was systematically changed to an alanine. Peptide epitopes with altered amino acids outside T cell contact residues were still recognized by T cells induced by PSNPs-SYIPSAEKI (KI) vaccines, albeit at lower levels, except for the variant SYIPSAAKI (A7). PSNPs-SYIPSAAKI vaccines further elicited high responses to the index KI peptide. None of the epitopes displayed altered peptide ligand (APL) antagonism in vitro, and re-stimulating SYIPSAEKI and SYIPSAAKI together synergistically enhanced IFN-γ production by the T cells. These results show epitope variation in non-TCR recognition residues can have effects on T cell reactivity, suggesting that such natural variation may also be driven by immune pressure. Additionally, when re-modelling peptides to enhance the cross-reactivity of vaccines, both TCR recognition and non-recognition residues should be considered.